Pregnant female and near term embryos of the honeycomb stingray Himantura uarnak (Chondrichthyes - Dasyatidae) from Mersin Bay, northeastern Mediterranean - Basusta, Nuri; Basusta, Asiye (Natl Centre Marine Research, 2023)
The honeycomb stingray Himantura uarnak (Gmelin, 1789) is one of the non-indigenous species in habiting eastern Med-iterranean Sea. A single pregnant female was accidentally captured in March 2022 in the commercial purse seiner fishing. The taxonomic identification of this species has been confirmed by using DNA barcoding. The present study provides the first account of a gravid female and near term embryos H. uarnak, captured off the coast of Mersin Bay, Turkiye. Data of near term embryos, suggests that parturition occurred in either end of March or early April.
Keywords: Himantura uarnak; Lessepsian Species; Mersin Bay; Mediterranean Sea; Reproduction